Clinico-Epidemiological Profile and Utility of Diagnostic Techniques in Immunocompetent Children with Cryptosporidium Diarrhoea - Sadia Mansoor; Sumaiya Shamsi; Priyanka Shukla; Shrish Bhatnagar (Journal of Medical Sciences and Health, 2022)
Purpose: To assess the Clinical and Epidemiological profile of children 6 months to 5 years having Cryptosporidium diarrhoea and to compare the diagnostic accuracy of rapid diagnostic test (RDT) against modified acid-fast stain technique to detect Cryptosporidium in stool. Materials and Methods: Details of demography, presenting complaints, and detailed examination of children presenting with acute or persistent diarrhoea were recorded in a predesigned proforma. Two Stool samples were collected and examined same day by rapid antigen test and microscopy for presence of antigen or oocyst of cryptosporidium. Results: Out of the total of 280 samples tested, 40 (14.3%) samples were positive for Cryptosporidium. The prevalence of Cryptosporidium in children presenting with diarrhoea in our study came out to be 14.3%. Fever, vomiting and pain abdomen were the most common presenting complaints. Epidemiological factors like providing clean water, proper feeding and hygiene, and avoidance of overcrowding can help in reducing the burden of Cryptosporidium diarrhoea. Persistent diarrhoea was more common among cryptosporidium positive cases. Rapid detection kits enhance the detection rate and are sensitive as well as specific. It could be utilised as an aid in diagnosis of Cryptosporidium diarrhoea. Conclusion: The study shows that cryptosporidial diarrhoea is not uncommon in immunocompetent children. Improvement in personal hygiene, feeding practices and access to safe and potable water can help in reducing burden of this disease. Antigen detection kits aid in early diagnosis. Keywords: Paediatric cryptosporidiosis, Persistent diarrhoea, Sanitation, RDT in diarrhoea, Abdominal pain